Improving nitrogen contribution in maize post-tasseling using optimum management under mulch drip irrigation in the semiarid region of Northeast China - Hou, Yunpeng; Xu, Xinpeng; Kong, Lili; Zhang, Lei; Zhang, Yitao; Liu, Zhiquan (Frontiers in Plant Science, 2022)
Film-mulched drip irrigation has become an important strategy in maize cultivation in the semiarid region of Northeast China. Most farmers concentrate nitrogen (N) fertilizer use early in maize growth, which leads to low N use efficiency and large N losses. Therefore, a three-year (2018 to 2020) field experiment was conducted to determine the optimal N management strategy for maize under film mulch with drip irrigation in the semiarid region of Northeast China. The experiment included five treatments with the total amount of N fertilizer (210 kg N ha−1) applied in different proportions at sowing, sixth-leaf (V6), twelfth-leaf (V12), tasseling (VT), and blister (R2) stages of maize growth: N1, 100-0-0-0-0; N2, 50-50-0-0-0; N3, 30-50-20-0-0; N4, 20-30-30-20-0; and N5, 10-20-30-20-20. The control (CK) did not receive N fertilizer. Maize yield, N uptake and use, changes in soil inorganic N content, and N balance were investigated. Compared with the single basal application (N1), split-N applications (N2, N3, N4, N5) increased maize yield from 13.8% to 24.5% by increasing kernel number per ear and 1000-kernel weight and also improved N accumulation from VT to physiological maturity (PM) stages and its contribution to grain N uptake. In addition, compared with N1, split-N applications also decreased N losses by increasing inorganic N contents in the 0–40 cm soil layer and by decreasing N leaching in the 60–200 cm soil layer. Regression analysis demonstrated that N accumulation after the VT stage was positively related with maize yield. Among treatments, N4 had the highest yield, N recovery efficiency, agronomic efficiency, and partial factor productivity, with respective increases of 24.5%, 14.7 percentage point, 11.4 kg kg−1, and 11.4 kg kg−1 compared with those in N1. As a result, N losses were also reduced by 33.7% in N4 compared with those in N1. In conclusion, the split-N management strategy with four N applications under film-mulched drip irrigation has great potential to improve maize yield, increase N use efficiency, and reduce N loss in the semiarid region of Northeast China.